A familial incidence of Otosclerosis - Tlruvenkatachari (Journal of All India Institute of Speech and Hearing, 1970)
Carhart (1963) reports a family wherein two brothers were suffering from labyrinthine otosclerosis. Their mother had a long standing hearing loss and their own difficulties had been progressive since the ages of 11 and 15 res- pectively and the younger man exhibited a lower level of hearing loss. Their audiograms showed bilateral mixed hearing loss.